Interlinkages and indicators: novel assessment of water, sanitation and solid waste services in schools in two Ugandan towns - Farine, Charlotte; Lüthi, Christoph; Niwagaba, Charles Buregeya; Morgenroth, Eberhard; Narayan, Abishek Sankara (Frontiers in Water, 2025)
The status of Water, Sanitation, and Hygiene (WASH) in schools in sub-Saharan Africa remains dire. Only 46% have access to basic water services, 44% to basic sanitation services, and 26% to basic hygienic services. Although integrating these services with other water and waste streams could benefit service provision, a systematic methodology for such integration does not exist yet. This research approaches a first step–a methodology for an integrated assessment of water, sanitation, and solid waste management (SWM) services in schools. In addition, a modified version of the Joint Monitoring Program’s WASH service ladder for schools is provided for a detailed understanding of the service levels. A total of 16 schools from two small towns in Uganda are taken as case studies to identify the current service levels, interlinkages between the sectors as well as their enabling environment. Using surveys, stakeholder interviews, observations, and water quality measurements, the results show several cross-contamination pathways leading to exposure of pupils to pathogens. Finance and policies are major inhibitors of positive interlinkages and limited skills and capacities amplify negative interlinkages. The results emphasize the need for a shift toward further integrated planning of the water and waste services in schools and other institutions.